Clinical outcomes of radical surgery in patients with renal carcinoma and associated venous thrombosis: Single‐centre experience in a tertiary care institution. Issue 4 (12th December 2020) - Onal, Bulent; Simsekoglu, Muhammed Fatih; Gultekin, Mehmet Hamza; Demirdag, Cetin; Citgez, Sinharib; Erozenci, Ahmet
Abstract: Background: Renal carcinoma and associated venous thrombosis cause specific perioperative and postoperative challenges. We aimed to evaluate the factors affecting clinical outcomes in patients undergoing radical surgery because of renal carcinoma and associated venous thrombosis. Materials and methods: Hospital records were retrospectively reviewed to identify patients with renal carcinoma and associated venous thrombosis treated with radical surgery between 2006 and 2019. Preoperative, perioperative, and postoperative findings were analysed to determine the associations between clinical and survival outcomes. Overall and disease‐free survival were analysed by the Kaplan‐Meier method. Other associated prognostic variables were assessed using univariate and multivariate Cox regression analyses. Results: Thirty‐three patients with renal carcinoma and associated venous thrombosis were enrolled for this study. There were 15 (45.4%) patients with level I, five (15.2%) with level II, eight (24.2%) with level III, and five (15.2%) with level IV venous thrombosis according to the Mayo Clinic classification system. The median follow‐up was 35.6 months. In the univariate analysis, increased tumour size was associated with poor overall and disease‐free survival. Preoperative clinic M1 disease was associated with poor overall survival. A high Mayo Clinic thrombus level was associated with poor disease‐free survival. In the multivariate analysis, only tumour size and clinic M1 disease were independently correlated with poor overall survival. No independent statistically significant association was detected between thrombus level and survival outcomes. Conclusions: Although the thrombus level was not associated with overall and disease‐free survival, tumour size and clinic M1 disease were found to have an independent prognostic impact on overall survival.